2021
DOI: 10.1038/s41598-021-01622-7
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of contrast-enhanced 2D mammography in everyday clinical use

Abstract: Contrast-enhanced mammography (CEM) has shown to be superior to full-field digital mammography (FFDM), but current results are dominated by studies performed on systems by one vendor. Information on diagnostic accuracy of other CEM systems is limited. Therefore, we aimed to evaluate the diagnostic performance of CEM on an alternative vendor’s system. We included all patients who underwent CEM in one hospital in 2019, except those with missing data or in whom CEM was used as response monitoring tool. Three expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Irrespective of the strict study eligibility criteria applied, the results show that there was still considerable between-study heterogeneity with I 2 values higher than 80%. Although studies were performed on CEM systems by two vendors this probably did not contribute to the high I 2 values, since recent research showed that diagnostic accuracy of CEM is likely to be vendor system independent 38 . One source of the variation between study results could be methodological issues, such as differences in patient populations and variation in reader experience.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the strict study eligibility criteria applied, the results show that there was still considerable between-study heterogeneity with I 2 values higher than 80%. Although studies were performed on CEM systems by two vendors this probably did not contribute to the high I 2 values, since recent research showed that diagnostic accuracy of CEM is likely to be vendor system independent 38 . One source of the variation between study results could be methodological issues, such as differences in patient populations and variation in reader experience.…”
Section: Discussionmentioning
confidence: 99%